Understanding the challenges faced by adolescents and young adults with allergic conditions: A systematic review. Issue 8 (27th July 2020) - Vazquez‐Ortiz, Marta; Angier, Elizabeth; Blumchen, Katharina; Comberiati, Pasquale; Duca, Bettina; DunnGalvin, Audrey; Gore, Claudia; Hox, Valérie; Jensen, Britt; Pite, Helena; Santos, Alexandra F.; Sanchez, Silvia; et al.
Abstract: Background: Adolescence represents a vulnerable time for individuals with asthma and allergic conditions. They suffer an unexpected degree of morbidity. This systematic review aimed to understand the challenges faced by adolescents and young adults with these conditions. Methods: A systematic literature search was undertaken across eight databases. References were checked by two reviewers for inclusion. Study data were extracted, and their quality was assessed in duplicate. A narrative meta‐synthesis was undertaken. Results: A total of 108 papers describing 106 studies were retrieved, most focused on asthma. Five themes were identified across studies: (a) Health‐related quality of life—impairment was associated with poor disease control, psychosocial issues, adolescent‐onset allergic disease and female sex; (b) Psychological factors—asthma and food allergy were associated with anxiety and depression, atopic dermatitis was associated with suicidal ideation, and that parental emotional support may be protective; (c) Adherence—suboptimal adherence was associated with older age, barriers to medication usage, poor symptom perception and failure to take responsibility, and positive factors were routines, simpler treatment regimes, better knowledge and perceptions about medications; (d) Self‐management—facilitated by education, knowledge and a positive attitude; and (e) Supportive relationships—families could modify barriers to adherence and foster positive views about self‐management, adolescents suggested that their peers should be more involved in supporting them, and adolescents also wished to have support from nonjudgemental healthcare professionals. Conclusions: We have some understanding of the challenges faced by adolescents with asthma, less so for other allergic conditions. This knowledge will be used to support guidelines for managing adolescents.